Industrial Economics in Scandinavia: 1880-1980 - Nicolai J. Foss; Peter Møllgaard (Copenhagen Business School (CBS), Department of Economics, 2004)
Based on diverse research methods, we trace and map industrial economics research in Denmark, Norway and Sweden in the periode of 1880 to 1908. After describing this research in terms of key contributors, we argue that industrial economics developed rather unevenly in the Scandinavian countries. Danish research was mainly theoretical and strongly oriented towards the international context, whereas Norwegian research was largely industry analysis with a strong leaning towards managerial economics. Swedish research in industrial economics is very scant until the end of the 1960s.
hdl:10398/7539
Keywords: B10; B20; B30; D20; D40; L10; L20; L40; 330